An observational study of acupuncture and complementary treatments for major depression: Case series from a preliminary study of proposed collaborative care model - Sara Maria Tamayo; Tsu-Hsuan Wei; Liang-yu Chen; Wen-Chao Ho; Gil Ton; Yu-Chen Lee (Journal of Traditional and Complementary Medicine, 2022)
Background: Major depressive disorder is identified as a mood disorder characterized by episodically recurring and potentially life-threatening negative symptoms. It is currently important for study, as it involves high morbidity, mortality and prevalence, as well as unsatisfactory treatment results. Aim: Establish an outpatient model from an integrative approach promoting the diversified development of traditional Chinese and Western medicine cooperation, leading to a holistic intervention for patients with depression. Experimental procedure: Fifteen participants with moderate to severe depression were followed up for eight weeks in the Acupuncture Department of the China Medical University Hospital in Taichung, Taiwan, under a collaborative outpatient model that combined Western psychiatry and traditional Chinese medicine (TCM). Interdisciplinary Intervention included manual acupuncture twice a week (16 sessions), tai chi, yoga meditation, and nutritional assessment. Symptomatology was measured with primary outcomes (self-reporting via questionnaires) and secondary outcomes (heart rate variability [HRV] and blood samples to measure inflammation via high-sensitivity C-reactive protein [hs-CRP]). Results: The response rate was 80% (12/15 participants), with a statistically and clinically significant decrease in depression severity according to the 21-question Hamilton depression rating scale (HDRS21) (p < 0.001), the Beck Depression Inventory (BDI) (p < 0.003), and quality of life (QoL) questionnaires (p < 0.002). We found body constitution heterogeneity in the participants with major depressive disorder (MDD), predominantly blood stagnation and Qi stagnation (in 70% of participants). Conclusion: An interdisciplinary outpatient treatment method of complementary therapies can be applied successfully with pharmacological treatment in clinical practice to reduce depression symptomatology. Section: Physical/Mental practices. Taxonomy: Major Depressive Disorder, Collaborative healthcare Treatment, Observational study.